A study on the governance pathways of the Law of the Sea in response to climate change - Zeng, Wanping; Wang, Guihua (Frontiers in Marine Science, 2024)
The legal systems for ocean governance and climate change governance are based on the United Nations Convention on the Law of the Sea and the United Nations Framework Convention on Climate Change, respectively. However, due to differences in their negotiation backgrounds, legal scope, goals, and tasks, there is a lack of interaction between the two at the legal system level. The ocean plays a crucial role in regulating the Earth’s climate system, yet its value is often underestimated in the United Nations Framework Convention on Climate Change. The aim of this study is to analyze the effectiveness of the United Nations Convention on the Law of the Sea in addressing climate change. Specifically, we will examine the Convention’s ability to mitigate and adapt to climate change, and identify areas where it falls short, such as inadequate regulation of sea level rise, ocean acidification, and ocean fertilization. Based on this, proposals for governance paths from the perspective of the United Nations Convention on the Law of the Sea include developing the Agreement relating to the climate change and ocean governance and reinterpreting the United Nations Convention on the Law of the Sea in accordance with the Paris Agreement. The content should be adapted more flexibly to current climate change challenges, and provisions related to sea level rise and maritime boundaries should be reinterpreted to fill legal gaps. In addition, it is important to establish coordinated regulatory rules and framework agreements to address the issues of ocean fertilization and ocean acidification. Finally, to remedy the shortcomings in proving causation, scientific theories and due diligence obligations should be attributed. Through these measures, effective ocean law governance paths that address climate change can be explored.